'n Voorlopige navorsingsagenda vir die spirituele re-kapitalisasie van die werksplek - 'n prakties teologiese re-konstruksie? - J. A. van den Berg (Acta Theologica)
In this article practical theology is portrayed as a work-zone under construction. In order to understand the architecture associated with the construction work, the impotence of so called zombie categories and shell institutions are used to illustrate that practical theology needs to be re-constructed. This re-construction is being developed through reconsidering paradigm, epistemology and methodology operating within a relevant re-constructed practical theology. Theoretical principles are embodied in the use of the qualitative Delphi forecast method, documenting the consensus opinion of 10 informed participants on the possible role of spirituality within the workplace. Building on these accents, some markers are mapped for the further development of the so called recapitalisation of practical theology with emphasis on a possible meaning for the workplace. Future perspectives for the facilitation of spirituality in the workplace are mapped in conclusion.